2015
DOI: 10.5901/mjss.2015.v6n2s1p407
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Factors Affecting Community Participation towards Polio Immunization in Nigeria

Abstract: Several publications have been written and reviewed to urge efforts reducing the rate of infant morbidity and mortality throughout the world. Scientific innovations and research for efficient immunization has been able to reduce the spread of poliomyelitis across the world and make this vaccine preventable disease a history. However, immunization coverage and poliomyelitis disease eradication seems to be cost effective and has continued to falter in Nigeria (Nnenna et al, 2013)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The flexibility of FTHGs is such that every woman chooses where she wants to give birth to her child due to family background, culture, and beliefs that medical practitioners may not be able to handle [10]. This serves as an indicator to plan a program for FTHGs and educate them on remedies for the killer diseases, which will serve as the medium for awareness to mothers in their communities, as most of them are skeptical with different perceptions on the program (immunization) let alone of promoting it [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The flexibility of FTHGs is such that every woman chooses where she wants to give birth to her child due to family background, culture, and beliefs that medical practitioners may not be able to handle [10]. This serves as an indicator to plan a program for FTHGs and educate them on remedies for the killer diseases, which will serve as the medium for awareness to mothers in their communities, as most of them are skeptical with different perceptions on the program (immunization) let alone of promoting it [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Many people live under a poverty level of less than a dollar per day [14]. Studies showed about 216, 000 children die yearly, with an average of 600 per-day and 100,000 children liable to physical disability consequent of killer diseases [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 Community engagement has been beneficial and has encouraged the adoption of health services by individuals who have negative beliefs and attitudes by engaging them to discuss the basis of their beliefs and encouraging them to proffer solutions to issues they identified. 11 One successful example of community engagement in high-risk areas includes the 2014 engagement of 11 000 female community-based mobilisers in Nigeria to advocate for vaccine uptake in northern Nigeria. 12 This resulted in over 322 000 newborns referred for routine immunisation and over 32 000 malnourished children referred for appropriate care.…”
Section: Introductionmentioning
confidence: 99%
“…In order to build up the country, communities will be one of an important part. A few past studies focus on certain community like research by [1] which was look at the factors affecting community participation towards polio immunization in Nigeria. In [2] also focus on quality of life community that participated in homestay program in Malaysia.…”
Section: Introductionmentioning
confidence: 99%